Crime of feminicide from a gender (Research, Society and Development, 2022)
This article aims to discuss the importance of creating a qualifying figure for femicide by Law No. 13,104/15, for a policy to combat and punish gender violence. Currently, there are several policies to combat gender violence in Brazil, with emphasis on Law No. 11,340/06, popularly known as the Maria da Penha Law. This legislation provides for a series of protection measures to guarantee victims protection against their aggressors, given that gender violence tends to cause serious damage to the psychic and emotional health of victims, but it does not mention cases of homicide committed within the scope of family relationships and/or motivated by discrimination against women. This gap was remedied by Law No. 13,104/15, which brought changes to the Penal Code and the Law on Heinous Crimes. This research was carried out following a qualitative approach, through a bibliographic research. To this end, we initially sought to present a brief historical context on the socio-family and legal treatment given to women, as well as the main forms of domestic and family violence, described in Law No. 11,340/06. It also addresses the main national and international regulatory frameworks to combat gender violence. Then, an analysis of the crime of femicide is made, starting from the changes brought about in the criminal legal system. It found that these legislative changes are an important instrument for a more severe punishment of murderers, as well as perfecting the policy to combat gender violence.